Comparing neurostimulation technologies in refractory focal-onset epilepsy. Issue 11 (11th August 2016) - Gooneratne, Inuka Kishara; Green, Alexander L; Dugan, Patricia; Sen, Arjune; Franzini, Angelo; Aziz, Tipu; Cheeran, Binith
Abstract : For patients with pharmacoresistant focal epilepsy in whom surgical resection of the epileptogenic focus fails or was not feasible in the first place, there were few therapeutic options. Increasingly, neurostimulation provides an alternative treatment strategy for these patients. Vagal nerve stimulation (VNS) is well established. Deep brain stimulation (DBS) and cortical responsive stimulation (CRS) are newer neurostimulation therapies with recently published long-term efficacy and safety data. In this literature review, we introduce these therapies to a non-specialist audience. Furthermore, we compare and contrast long-term (5-year) outcomes of newer neurostimulation techniques with the more established VNS. A search to identify all studies reporting long-term efficacy (>5 years) of VNS, CRS and DBS in patients with refractory focal/partial epilepsy was conducted using PubMed and Cochrane databases. The outcomes compared were responder rate, percentage seizure frequency reduction, seizure freedom, adverse events, neuropsychological outcome and quality of life. We identified 1 study for DBS, 1 study for CRS and 4 studies for VNS. All neurostimulation technologies showed long-term efficacy, with progressively better seizure control over time. Sustained improvement in quality of life measures was demonstrated in all modalities. Intracranial neurostimulation had a greater side effect profile compared with extracranial stimulation, though all forms of stimulation are safe. Methodological differences between the studies mean that direct comparisons are not straightforward. We have synthesised the findings of this review into a pragmatic decision tree, to guide the further management of the individual patient with pharmacoresistant focal-onset epilepsy.